The influence of rice plant age on susceptibility to the rice water weevil, Lissorhoptrus oryzophilus. (4th July 2012) - Stout, M. J.; Hamm, J. C.; Abbe, I.; Bergeron, C.
Abstract Plant age‐ and plant stage‐related changes in the resistance of rice, Oryza sativa, to its most important insect pest in the US, the rice water weevil (Lissorhoptrus oryzophilus), were investigated in a series of field and greenhouse choice and no‐choice studies. Rice plants were susceptible to infestation by rice water weevils over a broad range of plant ontogenetic stages, from at least the early vegetative stage to well into the reproductive stage. There was, however, a clear preference expressed by rice water weevils in both choice and no‐choice experiments for plants in (or nearly in) the tillering stage of development, with pre‐tillering and reproductive stage plants less preferred. The relationship between rice plant age and susceptibility to weevils is thus nonlinear. This study constitutes one of the most thorough studies to date of the relationship in a grass species between plant age and susceptibility to herbivores. The results provide a biological explanation for observed patterns of weevil infestations and a rationale for the cultural practice of delayed flooding.